Vertical transmission of Coronavirus Disease - A difficult diagnostic challenge - Soares,Elisa Sofia Oliveira (2022)
Abstract The aim of this case report is to describe a rare case of vertical transmission of SARS-CoV2, in a mother with atypical symptoms. We describe a case of an emergent cesarean section, at 29 weeks, due to pathological cardiocographic tracing. Pregnant was attended because of dermatologic symptoms and SARS CoV-2 RT-PCR was positive. Newborn RT-PCR was negative on umbilical cord blood and nasopharyngeal swabs. On the 9th day, due to hemodynamic instability and respiratory depression, the newborn died. Despite previous negative tests, RT-PCR for SARS-CoV2 was positive on fetal and placental tissues.